Regional disparity in the Caribbean : the case of the CARICOM LDCs. - Hosten-Craig, Jennifer (1990)
Argues that CARICOM has provided only limited developmental opportunities for its member states, particularly the LDCs. Suggests that the hope for deepening the regional integration has shifted from CARICOM to the OECS.